Depósitos tecnogênicos construídos na bacia do Ribeirão Anicuns - Goiânia: implicações ambientais e de saúde - Silva, Elizabeth Soares da (2008)
Through productive activity, man has acted on the nature of the item has been proposed a new geological period to characterize the present time, which would be the Period Quinário or Technogene . Along with the suggestion for a new period, the term also came technogenic deposit, which features a vast amount of deposits formed as a result of human action. Can be classified as: constructed, induced and modified. This work is held to study the deposits built. More properly, identify and characterize the deposits built tecnogênicos found in the basin of Stream Anicuns in the city of Goiânia - GO and present the implications for the environment and human health. How to offer food abundant and ease of shelter, attract many insects and animals that can spread directly or indirectly many diseases, in addition to degrade the landscape, the soil and contaminate surface water and groundwater. In this study were identified nineteen deposits in the basin of Stream Anicuns, such as the results, these deposits show great diversity of debris, some may take millions of years to decompose, others have substances harmful to the soil and health. The population of Goiânia, is already realizing the impact of these deposits. The resolution of these problems hampered in the absence of educational programmes capable of involving the community and lack of public policies geared to the current urban society.